Pan-cancer analysis of the prognostic and immunological roles of DEAD-box helicase 5 (DDX5) in human tumors - Liu, Shixuan; Liu, Yanbin; Zhang, Xi; Song, Xuanlin; Zhang, Boxiang; Zhang, Yong (Frontiers in Genetics, 2022)
Background: Recent studies have demonstrated the significance of the DEAD-box helicase 5 (DDX5) gene, which is involved in pathways concerning the modification of RNA structures. DDX5 functions as a coregulator of cellular transcription and splicing, and participates in the processing of small noncoding RNAs. The aberrant regulation of DDX5 expression possibly plays a significant role in the genesis of cancer. However, there are no comprehensive pan-cancer studies on DDX5. This study is the first to conduct a pan-cancer analysis of DDX5 for aiding the diagnosis and treatment of cancer. Methods: The gene expression, genetic alterations, protein phosphorylation, promoter methylation, immune infiltration, and enrichment analyses of DDX5 were performed using data retrieved from The Cancer Genome Atlas (TCGA), Genotype-tissue Expression (GTEx), Human Protein Atlas (HPA), Tumor Immunological Estimation Resource 2.0 (TIMER2.0), Gene Expression Profiling Interactive Analysis (GEPIA), DNA methylation interactive visualization database (DNMIVD), and Search Tool for the Retrieval of Interaction Genes/Proteins (STRING). Data analyses were performed with the R software and other webtools. Results: The expression of DDX5 mRNA decreased significantly in 17 cancer types, but increased significantly in 8 cancer types. The enhanced expression of DDX5 mRNA in the tumor samples was related to decreased overall survival (OS), progression-free interval (PFI), and disease-specific survival (DSS) in 3 cancers, but increased OS, PFI, and DSS in other cancers. The DNA promoter methylation level was significantly reduced in 8 cancer types, and there were exceptions in the methylation levels of the DDX5 promoter in 4 cancer types. The expression of DDX5 mRNA was highly correlated with the infiltration of CD8+ T cells, cancer-associated fibroblasts, and B cells in a wide variety of malignancies. The findings revealed a strong association between DDX5 and its co-expressed genes in numerous cancer types. Enrichment analysis suggested that DDX5 was associated with multiple cellular pathways, including RNA splicing, Notch signaling pathway, and viral carcinogenesis, which was consistent with the results of previous studies. Conclusions: The findings obtained herein provide further information on the oncogenic potential of DDX5 in diverse tumor types. We propose that DDX5 has important roles in tumor immunity and the diagnosis of cancer.